Phytochemical Profile and Sun Protection Efficacy of whole plant of Saccharumspontaneum Extracts - Vaishali Sharma,; Zulphikar Ali,; Bhupendra Chauhan,; Ranjeet Singh, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Plant extracts have been evaluated to be potential sunscreen ingredients due to their antioxidant activity and capacity to absorb ultraviolet radiation.The aim of the current study is to analyze the sun protection factor activity of several extracts ofSaccharumspontaneum. Whole plant of Saccharumspontaneum was extracted using water, petroleum ether and applying the method of the cold maceration. Preliminary phytochemical screening of Saccharumspontaneum extracts was studied.Sun-protective activity of the various Saccharumspontaneum extracts was evaluated by determining the sun protection factor utilizing the UV spectroscopic method. The phytochemical screening showed the presence of various phytoconstituentsin all extracts of Saccharumspontaneum.The sun protection factor of the different extracts were found to be,3.728±0.016, 2.339±0.003, and 9.402±0.022respectively.This result implies that the extracts may be used in various ratios and combinations to produce photoprotective formulations that have a synergistic or additive impact.